2010
DOI: 10.1093/nar/gkq783
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and viral chromatin proteins are positive factors in the regulation of adenovirus gene expression

Abstract: The adenovirus genome forms chromatin-like structure with viral core proteins. This complex supports only a low level of transcription in a cell-free system, and thus core proteins have been thought to be negative factors for transcription. The mechanism how the transcription from the viral DNA complexed with core proteins is activated in infected cells remains unclear. Here, we found that both core proteins and histones are bound with the viral DNA in early phases of infection. We also found that acetylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
134
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(144 citation statements)
references
References 45 publications
9
134
1
Order By: Relevance
“…H3.3 continued to be the predominant H3 variant associated with hdAd until at least 24 hpi (data not shown). Recent work has shown that histones are found to be associated with wild-type Ad DNA as early as 1 hpi and that all members of the nucleosome, H2A/H2B, H3 and H4, are present (31). These data, and previous work by others (5,13,14,66), strongly suggest that hdAd and Ad DNA are wrapped in nucleosomes within the infected cell nucleus.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…H3.3 continued to be the predominant H3 variant associated with hdAd until at least 24 hpi (data not shown). Recent work has shown that histones are found to be associated with wild-type Ad DNA as early as 1 hpi and that all members of the nucleosome, H2A/H2B, H3 and H4, are present (31). These data, and previous work by others (5,13,14,66), strongly suggest that hdAd and Ad DNA are wrapped in nucleosomes within the infected cell nucleus.…”
Section: Discussionsupporting
confidence: 56%
“…These data, and previous work by others (5,13,14,66), strongly suggest that hdAd and Ad DNA are wrapped in nucleosomes within the infected cell nucleus. The observation that both VII and histones can be found bound to the same DNA molecule (31) suggests that the processes of core VII eviction and histone placement may be coincident. The cellular chaperones implicated in removing VII from the incoming viral DNA, TAFI-III also known as B23/nucleophosmin (45), pp32 (77), SET (37), and NAP-1 (30), have also been implicated in the removal of protamines from incoming sperm DNA and in the assembly of sperm DNA into chromatin (38,52,60).…”
Section: Discussionmentioning
confidence: 99%
“…During herpesvirus lytic infection, the viral genomes are associated with histones immediately after injection into the nucleus, and viral proteins are required to enhance histone acetylation to allow for efficient viral gene expression (40)(41)(42)(43)(44). Moreover, studies of infection by an adenovirus have shown that viral proteins mediate the transcriptional activation of viral promoter regions (45)(46)(47). In this work, we first observed that the progress of CPV infection was accompanied by the enrichment of H3 histones in the enlarged APAR body area.…”
Section: Discussionmentioning
confidence: 79%
“…Since this discovery, the importance of the chromatinization of the viral genome in DNA damage (30) and transcription control (31,32) has become increasingly apparent. Previous work from our lab has further shown regulatory roles for chromatin modifications within the promoter regions of the viral genome (6).…”
Section: Discussionmentioning
confidence: 99%